Neurocognitive Functioning in Schizophrenia and during the Early Phases of Psychosis: Targeting Cognitive Remediation Interventions. (5th September 2013) - Zaytseva, Yulia; Korsakova, Natalya; Agius, Mark; Gurovich, Isaac
Abstract : Recent interest in the early course of schizophrenia accentuated altered cognition prior to the onset. Ultrahigh risk (UHR) individuals with attenuated positive symptoms and transient psychotic episodes demonstrate neurocognitive deficits across multiple domains such as memory, executive functioning, and processing speed which are consistent with similar disturbances identified in patients with a first episode of schizophrenia. Cognitive remediation (CR) approaches representing a broad set of activities are aimed to restore or improve cognitive functioning. CR proved to be effective in modulating the cognitive dysfunction in schizophrenia but is rarely used in ultrahigh risk individuals. From the clinical prospective, a better understanding of cognitive functioning in at-risk states is essential for the development of optimal early intervention models. In the review, we highlight the intervention targets, notably the specific cognitive deficits in at risk individuals which preceed the transition to psychosis and emphasize the need of the additional studies using CR approaches in UHR group aiming to enhance cognition and therefore mediate functional improvement.